Evaluation on the Efficiency of Biomass Power Generation Industry in China - Jingqi Sun; Dong Sun; Sen Guo (The Scientific World Journal)
As a developing country with large population, China is facing the problems of energy resource shortage and growing environmental pollution arising from the coal-dominated energy structure. Biomass energy, as a kind of renewable energy with the characteristics of being easy to store and friendly to environment, has become the focus of China’s energy development in the future. Affected by the advanced power generation technology and diversified geography environment, the biomass power generation projects show new features in recent years. Hence, it is necessary to evaluate the efficiency of biomass power generation industry by employing proper method with the consideration of new features. In this paper, the regional difference as a new feature of biomass power generation industry is taken into consideration, and the AR model is employed to modify the zero-weight issue when using data envelopment analysis (DEA) method to evaluate the efficiency of biomass power generation industry. 30 biomass power generation enterprises in China are selected as the sample, and the efficiency evaluation is performed. The result can provide some insights into the sustainable development of biomass power generation industry in China.